Households contaminated by environmental tobacco smoke: sources of infant exposures. Issue 1 (25th February 2004) - Matt, G E; Quintana, P J E; Hovell, M F; Bernert, J T; Song, S; Novianti, N; Juarez, T; Floro, J; Gehrman, C; Garcia, M; Larson, S
Abstract : Objectives: To examine (1) whether dust and surfaces in households of smokers are contaminated with environmental tobacco smoke (ETS); (2) whether smoking parents can protect their infants by smoking outside and away from the infant; and (3) whether contaminated dust, surfaces, and air contribute to ETS exposure in infants. Design: Quasi-experiment comparing three types of households with infants: (1) non-smokers who believe they have protected their children from ETS; (2) smokers who believe they have protected their children from ETS; (3) smokers who expose their children to ETS. Setting: Homes of smokers and non-smokers. Participants: Smoking and non-smoking mothers and their infants ⩽ 1 year. Main outcome measures: ETS contamination as measured by nicotine in household dust, indoor air, and household surfaces. ETS exposure as measured by cotinine levels in infant urine. Results: ETS contamination and ETS exposure were 5–7 times higher in households of smokers trying to protect their infants by smoking outdoors than in households of non-smokers. ETS contamination and exposure were 3–8 times higher in households of smokers who exposed their infants to ETS by smoking indoors than in households of smokers trying to protect their children by smoking outdoors. Conclusions: Dust and surfaces in homes of smokers are contaminated with ETS. Infants of smokers are at risk of ETS exposure in their homes through dust, surfaces, and air. Smoking outside the home and away from the infant reduces but does not completely protect a smoker's home from ETS contamination and a smoker's infant from ETS exposure.